National culture and corporate investment - Shao, Liang; Kwok, Chuck C Y; Zhang, Ran (Journal of International Business Studies, 2013)
We explore the relation between individualism and horizons and types of corporate investment, based on individualism’s implications for risk taking. We find that firms in individualistic countries invest more in long-term (risky) than in short-term (safe) assets. Moreover, the effect of individualism on long-term investment hinges on R&D: firms in individualistic countries invest more in R&D projects but not more in physical assets. To test whether risk taking is the channel through which individualism works, we employ two-stage ordinary least squares and other analyses to nullify alternative explanations, such as: (1) uncontrolled institutions determine both individualism and R&D; and (2) firms in individualistic countries invest more in R&D because they have higher investment efficiency, or pick less-risky R&D projects. We further find that individualistic firms tend to employ excess cash to increase R&D rather than increase dividends, and R&D decisions are less reliant on internal financing but more responsive to growth opportunities in individualistic countries.